Ultrafast high-temperature sintering of dense and textured alumina - Behera, Rohit Pratyush (2022)
Crystallographic texture engineering in ceramics is essential to achieve direction-specific properties. Current texture engineering methods are time-consuming, energy extensive, or can lead to unnecessary diffusion of added dopants. Herein, we explore ultrafast high-temperature sintering (UHS) to prepare dense and textured alumina using templated grain growth (TGG). From a slurry containing alumina microplatelets coated with Fe3O4 nanoparticles dispersed in a matrix of alumina nanoparticles, green bodies with oriented microplatelets were prepared using magnetic assisted slip casting (MASC). The effects of the sintering temperature, time and heating rate on the density and microstructure of the obtained ceramics were then studied. We found that TGG occurs for a temperature range between 1640 and 1780 °C and 10 s sintering time. Sintering at 1700 °C for 10 s led to dense and textured alumina with anisotropic grains thanks to the Fe3O4 coating, which did not have the time to diffuse. The highest texture and relative density were obtained with a heating rate of ~5,500 °C/min, leading to texture-dependent anisotropic mechanical properties. This study opens new avenues for fabricating textured ceramics in ultra-short times.